Deliberative Democracy through Public Dialogue: A Case Study of Road Development in Kampung Bandungsari RW 04, Tambangan Village, Mijen District, Semarang City - Annaz, Reza Allifia; Astuti, Retno Sunu; Kismartini, Kismartini (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Public dialogue serves as a two-way communication channel through public spaces to identify community needs. This research is motivated by efforts to address road issues in Kampung Bandungsari through public dialogue. The active participation of Kampung Bandungsari residents aligns with Jurgen Habermas's principles of deliberative democracy, as it leads to agreements that accommodate public interests. The research methodology employed is qualitative. Data collection was conducted through interviews and observations. Purposive sampling was used to select informants for this study. The research findings demonstrate that the active participation of Kampung Bandungsari residents in this process resulted in agreements that accommodate public interests. Field observations reveal that public dialogue in road construction in Kampung Bandungsari adheres to the principles of deliberative democracy.